Explain the factors affecting the development of sports entrepreneurship; Sociological and ecological approach - Nima Hasanzadeh; Zahra Sohrabi (Islamic Azad university, Isfahan Branch, 2022)
Objective: The purpose of this study was to carefully study the past and present process, opportunities and threats of the external environment in analyzing the process of sports entrepreneurship in Ardabil.Methodology: The method of the present research is descriptive-analytical. The statistical population of this study consisted of specialists (professors), experts, experts and sports entrepreneurs of Ardabil province. Thirty people were selected as a statistical sample through purposive sampling. In this study, the PESTLE model was used to identify the factors affecting the development of sports entrepreneurship in Ardabil.Results: Factors affecting the development of entrepreneurship were identified from six perspectives (economic, socio-cultural), (environmental and climatic), (legal and legal), technological factors and political factors.The importance of the entrepreneurship debate is such that economists consider entrepreneurs as the engine of economic growth and development of society and scientists consider their management as one of the most important factors of organizational change and innovation in the present age. And will have variety. Increasing sponsorships and sports promotion will increase the economic prosperity that has provided the basis for activities and production of industries in Ardabil province, as well as the establishment of production factories and the construction of infrastructure for commercial and cultural centers. The leverage of sports for advertising will provide a platform for hardware and reduce costs and ultimately productive use.Sports entrepreneurship recognizes existing, creatable, or discoverable opportunities in the field of sports and uses those opportunities to create emerging entrepreneurial activity. Also, creating sports culture in the community and identifying sports culture and the existence of social capital, as well as extensive advertising and creating effective cultural advertisements can promote health and social vitality and stimulate social communication and create social dignity through sports for Ardabil province in the field of sports entrepreneurship. Creates. Management of sports venues and facilities is another field of sports that has the necessary ground for entrepreneurship. Stadiums, stadiums, swimming pools, racetracks and all kinds of sports are suitable for the sports venue, which makes the need for creative and efficient management unavoidable. Each of these departments requires specific managerial skills.Due to the fact that Ardabil province is cold and has suitable weather conditions for winter sports, and also due to the humidity and altitude of Ardabil province and the suitable climate for using some cold weather disciplines, it can improve the environmental and climatic conditions affecting entrepreneurship development. As well as weather conditions and tourism attraction can be a platform for adventure sports tourism, as well as an increase in recreation centers and shopping centers in recreational areas.Observance of regulations in all aspects of sports, as well as determining legal plans for entrepreneurship development, as well as creating classes and workshops, and determining executive and legal programs and training classes, including legal factors affecting entrepreneurship development, such as long-term lending for sports goods and Entrepreneurship protection laws and legal protections and compliance with regulations are among the things that can affect the development of entrepreneurship in Ardabil province.Considering that today, with the arrival of new technologies in the field of sports, new disciplines have emerged that have been of particular interest to adolescents and young people, as well as the use of world-class technology and the use of state-of-the-art technology for the private sector. Effective and efficient for the development of entrepreneurship can be effective in creating a sports technology software platform and the development of sports entrepreneurship in Ardabil province. Also, suitable facilities in clubs and advanced equipment and increasing the number of equipped gyms can be effective in creating a hardware platform for sports technology and the development of sports entrepreneurship in the province. The use of advertising in cyberspace can also be one of the technological factors affecting the development of sports entrepreneurship in Ardabil province.Given that today's organizations need entrepreneurial staff and entrepreneurship is a turning point in the path, so the country's sports organizations need efficient managers and employees to be able to achieve their goals, managers can use job leadership style can job satisfaction Organizational commitment, entrepreneurial behavior and consequently increase the productivity of their organization. Also, talent identification of active forces and ultimately meritocracy can be one of the political factors affecting the development of entrepreneurship in public sports in Ardabil province. Also, reducing administrative barriers and bureaucracies and supporting departments of domestic production units and the existence of popular government and ethnicities and creating infrastructure and investments, as well as attracting investments and separating women and men sports and accepting hosting competitions are among the political factors affecting the development of public sports entrepreneurship in Ardabil province.Conclusion: Entrepreneurship plays a very key role in the economic and sustainable development of all societies. It seems that the problem of unemployment in society has become so large that only by creating a new market in the economy can create jobs for this volume of unemployed, a market that in addition to creating employment on a large scale, can also increase economic growth and development of the country. Guarantee. The need of the sports community and the labor market for efficient human resources and entrepreneurship requires that great and positive steps be taken in the country for the education and training of individuals. To achieve such goals in training and educating the workforce and injecting it into the labor market, the production of sports equipment and sports organizations and sports organizations must be planned in a way that is consistent and appropriate coordination between what is learned and the needs of the sports community and learners.